Advancing Pancasila Through Community Engagement: The Contribution of Universities to Ideological and National Awareness in Kenteng Village - Arifin, Ridwan; Riyanto, R. Benny; Fibrianti, Nurul; Karsinah, Karsinah (Indonesian Journal of Advocacy and Legal Services, 2024)
This paper explores the role of universities in advancing Pancasila as a guiding ideology through community engagement in Kenteng Village. As Indonesia faces challenges in maintaining national identity and unity, the significance of Pancasila— the nation’s foundational philosophical framework—cannot be overstated. The study examines a collaborative program initiated by a local university aimed at fostering ideological understanding and enhancing national awareness among villagers. Through workshops, seminars, and hands-on activities, university students and faculty worked closely with the Kenteng community to facilitate discussions on Pancasila values, encouraging active participation in civic life. The program also aimed to empower villagers by equipping them with skills and knowledge to promote social cohesion and resilience. The findings indicate that the initiative not only deepened the community's appreciation for Pancasila but also strengthened ties between the university and the village. Participants reported increased awareness of national issues and a stronger commitment to local governance and community development. This case study demonstrates that effective community engagement by universities can serve as a model for similar initiatives across Indonesia, reinforcing the importance of Pancasila in contemporary society. Ultimately, the paper advocates for a more structured approach to university-community partnerships, highlighting their potential to cultivate a deeper understanding of national identity and values among future generations.